Pop of the bumpy mummy - Cummings, Troy (New York, NY : Branches, Scholastic Inc., 2015)
Alexander's class is going on a sleepover at the Stermont Museum, but something is stealing bright, shiny objects from all over town, including the museum's treasured Ruby Scorpion, and on the night of the visit the young monster hunters finally confront the town's newest monster--a warrior covered entirely by bubble-wrap.
460
Keywords: Monsters -- Juvenile fiction; Elementary schools -- Juvenile fiction; Museums -- Juvenile fiction; Horror tales